PEMBAHASAN SOAL-SOAL UNTUK MENGHADAPI UJIAN MASUK PERGURUAN TINGGI DAN PELUANG UNTUK MASUK DUNIA KERJA BIDANG GEOLOGI DAN TAMBANG PADA SISWA SMK SABUMI BANJARBARU - Jarwanto, Jarwanto (Nusantara Hasana Journal, 2024)
This community service activity is entitled Discussion of Questions to Face the College Entrance Exam and Opportunities to Enter the World of Work in the Field of Geology and Mining for Students of SMK Sabumi Banjarbaru. Community Service Activities (PKM) for SMK Sabumi Mining students aim to provide real benefits both for the students themselves and for the surrounding community. The method of implementing the activity is carried out by means of lectures and practices related to college entrance exam questions and opportunities to enter the world of work in the fields of geology and mining. The results of this activity are that participants have knowledge and understanding in earth science and mining. Participants have knowledge and understanding in preparing students for internships and entering the world of work and will continue their undergraduate studies. Participants are given tips on working while studying, especially studying at the University of AKPRIND Indonesia by entering the employee class.